Hip arthrogram parameters predict radiographic outcomes of patients with developmental dysplasia of the hip treated by closed reduction - Tan, YunFei; Zhao, Wei; Wei, MinRong; He, Yi; Deng, HuaJun; Su, DaiWei; Zhu, WuHui; Wu, YuQian; Shen, Hao; Li, YiQiang (Frontiers in Pediatrics, 2024)
To investigate the relationship between intraoperative hip arthrogram parameters and residual acetabular dysplasia (RAD) and avascular necrosis of the femoral head (AVN) in children with developmental dysplasia of the hip (DDH) treated by closed reduction.Authors retrospectively analyzed the data of 102 patients (110 hips, mean age 14.6 months ± 4.7 months) with DDH treated by closed reduction. Hip arthrogram was routinely performed during the operation. The femoral head coverage rate (FHC), medial pool distance of hip (MPD), labrum inversion and reduction quality classification were evaluated under hip arthrogram. At the last follow-up, the presence of RAD and AVN was assessed on radiographs. The relationship between each arthrogram parameter and RAD as well as AVN was investigated using t-test, chisquare test, and logistic regression.The overall FHC and MDP averaged 42.2% ± 12% and 8.1% ± 11.7%, respectively. There were 80 hips (72.7%) with labrum inversion and 30 hips (27.2%) without. The reduction quality was type A in 57 hips (51.8%), type B in 28 hips (25.4%), and type C in 25 hips (22.7%). Thirty-two hips (29%) were in the RAD group and 78 hips (71%) were in the recovered group according to whether pelvic osteotomy was performed or not and according to the last Severin grade. FHC was significantly higher in the recovered group than in the RAD group (P = 0.014). There was no significant difference in sex, age at reduction, side, preoperative AI, IHDI classification, followup time, quality of reduction, MDP, and proportion of labrum inversion between the recovered and RAD groups. Logistic regression analysis showed that only FHC was a risk factor for RAD. The incidence of AVN above type II was 11.8% in this group of patients, and the incidence of AVN was significantly higher in patients with labrum inversion (23.2%) than in those without (7.5%) (P = 0.041). Logistic regression analysis showed that labrum inversion was a risk factor for AVN.The FHC measured under arthrogram can predict the occurrence of RAD after closed reduction of DDH, while MDP, reduction quality classification, and labrum inversion are of little significance. Labrum inversion is a risk factor for AVN.